2007
DOI: 10.1002/bit.21735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solution pH on protein transmission and membrane capacity during virus filtration

Abstract: Although virus filtration is now an integral part of the overall viral clearance strategy for the purification of many commercial therapeutic proteins, there is currently little understanding of the factors controlling the performance of the virus filters. The objective of this study was to examine the effects of solution pH on protein transmission and capacity during virus filtration. Data were obtained using bovine serum albumin as a model protein with Viresolve 180 membranes oriented with both the skin-side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Previous studies (Bakhshayeshi & Zydney, 2008;G. R. Bolton, Spector, & LaCasse, 2006;Dishari et al, 2015;Hongo-Hirasaki, Komuro, & Ide, 2010;Rayfield et al, 2015;Wickramasinghe, Stump, Grzenia, Husson, & Pellegrino, 2010) show that buffer conditions, including pH, buffer type, and ionic strength could affect the filtration performance of the virus filters.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Bakhshayeshi & Zydney, 2008;G. R. Bolton, Spector, & LaCasse, 2006;Dishari et al, 2015;Hongo-Hirasaki, Komuro, & Ide, 2010;Rayfield et al, 2015;Wickramasinghe, Stump, Grzenia, Husson, & Pellegrino, 2010) show that buffer conditions, including pH, buffer type, and ionic strength could affect the filtration performance of the virus filters.…”
Section: Introductionmentioning
confidence: 99%
“…A few years later, Malone et al [11] demonstrated that the hindered diffusion coefficient of latex particles through synthetic track-etched mica membranes was significantly reduced at low salt concentrations, a phenomenon that they attributed to the stronger electrostatic interactions at low ionic strength. Subsequent studies extended these observations to pressure-driven filtration of charged proteins through a range of commercial ultrafiltration membranes with different surface charge characteristics and under different solution conditions [6,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 90%
“…Filtration through virus retentive filters is currently a key unit operation during the production of biopharmaceuticals [27][28][29][30]. Careful process design and appropriate validation are critical for the successful implementation and performance of virus retentive filters [13].…”
Section: Viral Filtrationmentioning
confidence: 99%